Effect of fluoridated varnish and silver diamine fluoride solution on enamel demineralization: pH-cycling study Efeito do verniz fluoretado e da solução de diamino fluoreto de prata na desmineralização do esmalte: estudo utilizando modelo de ciclagem de pH - Alberto Carlos Botazzo Delbem; Maurício Bergamaschi; Kikue Takebayashi Sassaki; Robson Frederico Cunha (University of São Paulo, 2006)
OBJECTIVE: In the present investigation, the anticariogenic effect of fluoride released by two products commonly applied in infants was evaluated. METHODS: Bovine sound enamel blocks were randomly allocated to each one of the treatment groups: control (C), varnish (V) and diamine silver fluoride solution (D). The blocks were submitted to pH cycles in an oven at 37ºC. Next, surface and cross-sectional microhardness were assessed to calculate the percentage loss of surface microhardness (%SML) and the mineral loss (deltaZ). The fluoride present in enamel was also determined. RESULTS: F/Px10-3 (ANOVA, p<0.05) in the 1st layer of enamel before pH-cycling were (C, V and D): 1.61ª; 21.59b and 3.98c. The %SMH (Kruskal-Wallis, p<0.05) were: -64.0ª, -45.2b and -53.1c. %deltaZ values (ANOVA, p<0.05) were: -18.7ª, -7.7b and -17.3ª. CONCLUSION: The data suggested that the fluoride released by varnish showed greater interaction with sound enamel and provided less mineral loss when compared with silver diamine solution. OBJETIVOS: Este trabalho avaliou o efeito anticariogênico do flúor liberado por dois produtos comumente aplicados em crianças. MÉTODOS: Para isto, utilizaram-se blocos de esmalte de dentes bovinos distribuídos aleatoriamente em três grupos de tratamento: controle (C), verniz fluoretado (V) e solução de diamino fluoreto de prata (D). Os blocos foram submetidos à ciclagem de pH a 37ºC. Após, realizou-se o teste de microdureza de superfície (para o cálculo da % da perda de microdureza de superfície - %SML) e em secção longitudinal do esmalte (% de alteração da área mineral - %deltaZ) e a determinação do flúor presente no esmalte (F/P x 10-3). RESULTADOS: As concentrações de flúor (ANOVA, p<0,05) na 1ª camada do esmalte, antes da ciclagem de pH, foram (C, V e D): 1,6ª; 21,6b e 4,0c. Os resultados de %SML (Kruskal-Wallis, p<0.05) foram: -64,0ª, -45,2b e -53,1c. Os valores de %deltaZ (ANOVA, p<0.05) foram: -18,7ª, -7,7b e -17,3ª. CONCLUSÃO: Os dados sugerem que o flúor liberado pelo verniz apresentou maior interação com o esmalte promovendo menor perda mineral quando comparado à solução de diamino de prata.